Comments and reflections about third parties ownership against mortgages and inscribed real guarantees - Lama More, Héctor Enrique (2007)
in the national jurisprudence respect to the origin of the third party of the property or dominion against mortgages or moving guarantees registered, the possibility of admitting to proceeding the demand of third party of property against mortgages is analyzed in the presentarticle; and if in the assumption to admit it, the judicial veredict that arranges it can be appealed; it also explains the object and theexceptional case of origin of this demand, finalizing shaping his conclusions.